# A function satisfies the equation f(x + y) = f(x) f(y) for all x, y . Suppose that the function is differentiable at x = 0 and f’(0) = 2. Prove that f’(x) = 2f(x).

Given f(x) is differentiable at x = 0 and f(x) ≠ 0

And f(x + y) = f(x)f(y) also f’(0) = 2

To prove: f’(x) = 2f(x)

As we know that,

f’(x) =

as f(x+h) = f(x)f(h)

f’(x) =

f’(x) = …(1)

As

f(x + y) = f(x)f(y)

put x = y = 0

f(0+0) = f(0)f(0)

f(0) = {f(0)}2

f(0) = 1 { f(x) ≠ 0 ….given}

equation 1 is deduced as-

f’(x) =

f’(x) =

f’(x) = f(x)f’(0) {using formula of derivative}

f’(x) = 2 f(x) …proved { it is given that f’(0) = 2}

Rate this question :

How useful is this solution?
We strive to provide quality solutions. Please rate us to serve you better.
Related Videos
Super 10 Question: Check Your Knowledge of Maxima & Minima (Quiz)45 mins
Maxima & Minima in an interval60 mins
Questions Based on Maxima & Minima57 mins
Connection B/w Continuity & Differentiability59 mins
Questions based on Maxima & Minima in an interval59 mins
Check your Knowlege of Maxima & Minima ( Challenging Quiz)60 mins
Problems Based on L-Hospital Rule (Quiz)0 mins
When does a Maxima or Minima occur?48 mins
Interactive Quiz | Differentiability by using first principle59 mins
Interactive Quiz on Limits67 mins
Try our Mini CourseMaster Important Topics in 7 DaysLearn from IITians, NITians, Doctors & Academic Experts
Dedicated counsellor for each student
24X7 Doubt Resolution
Daily Report Card
Detailed Performance Evaluation
view all courses